The Effectiveness of Task Based Language Teaching (TBLT) Toward ESP Students’ Writing Achievement - Surti Milarisa (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
TBLT (Task Based Language Teaching) is an approach to language teaching that provides opportunities for students to engage in the authentic use of the target language through tasks. Writing is a process of formulating and organizing ideas in right words, delivering the writer’s purpose, and presenting them on a piece of paper. The objective of this research is to know the effectiveness of TBLT (Task Based Language Teaching) toward ESP students’ writing achievement at STIE Muhammadiyah Tanjung Redeb. Based on the research result on SPSS 24 calculation, it showed that t-value was 16,678, while t-table was 2,045 in the 5% of alpha significance level and 32 degrees of freedom (df). Thus, it indicates that the t-value is higher than t-table (16,678>1.693 and can be concluded that there was a significant difference between the two means. In addition, the alternative hypothesis (Ha) of the study was accepted and TBLT (Task Based Language Teaching) was an effective method in teaching writing.